The Capital Market Response to the Information Content of the Announcement of Indonesia Entering a Recession in 2020 and Free of Recession in 2021 in the Covid-19 Pandemic (Study on Company LQ-45) - Titis Siti Hikmawati; Harjum Muharam (Budapest International Research and Critics University, 2022)
The problem in this study is the existence of an inconsistent phenomenon of movement of the JCI value where at the time of announcement there was a recession that showed a negative economic growth for two consecutive quarters, namely the second quarter of 3.51% and the third quarter was 2.7% at In 2020, but the price of the JCI actually showed an increase, while when it was announced that Indonesia was free from recession, actually there was a decline trend at the JCI price. The purpose of this study was to analyze the differences in abnormal return and trading volume of the LQ-45 company's activity before and after the announcement of Indonesia entered and out of the recession. The population in this study were all financial data of the LQ-45 company in the semester 2 of 2020 and semester 2 of 2021 in the Indonesia Stock Exchange. The sample in this study was a company that was always incorporated in the LQ-45 index during the observation period. Data Collection Method is by document. The Data Analysis Method Used is a Different Different Test. Based on research, there are differences in the company's abnormal return before and after the announcement of Indonesia enters and is free of recession. There is a difference in trading of the company's activity volume before and after the announcement of Indonesia entered the recession. There is no difference in trading of the company's activity volume before and after the announcement of Indonesia is free of recession.